Systematic review of naturally occurring benzylisoquinoline alkaloids (2015–2024): phytochemistry, bioactivity and structure-activity relationship - Jing Liu; Tao Liu; Mu-Yan Liu; Hui-Hui Li; Xiao-Yu Zhao; Hui Zhang; Yan Ge; Ze-Dong Nan (Phytochemistry, 2026)

Nitrogen fertilization drives bacterial turnover versus fungal persistence for straw-derived C and N stabilization in a wheat-maize rotation - Guocui Ren; Xiuli Xin; Haowei Ni; Xianfeng Zhang; Lan Mu; Wenliang Yang; Shuchun Ge; Shaopu Pang; Anning Zhu (Soil and Tillage Research, 2026)

A modified SLD-ESD model for characterizing and predicting supercritical CH4 adsorption on shale at wide temperatures and pressures - Ke Hu; Chunkui Mu; Zhaolong Ge; Xiang Ao (Fuel, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

The Complete Mitochondrial Genome of a Newly Recorded Chinese Species of Diglyphus sabulosus (Hymenoptera: Eulophidae) and Insights into Its Phylogenetic Position - Lu-Chao Fang; Zhi-Qiang Ge; Ou-Yan Xi; Ze-Lu Mu; Hong-Ying Hu (Biochemical Genetics, 2026)

Study on plasma-activated supersonic water fog atomization and dust suppression performance - Mu Xinsheng; Ge Shaocheng; Zhang Tian; Jing Deji; Liu Shuo; Sun Liying; Pang Xingyu (Process Safety and Environmental Protection, 2026)

Effects of dietary serine addition to a high plant protein diet on growth performance, body composition, hepatosomatic histological structure and metabolism of taurine synthesis in juvenile turbot ( Scophthalmus maximus L.) - Guoshan Qi; Qinghui Ai; Xiaomin Jin; Ye Mu; Kangsen Mai; Muxiang Ge; Wenxiang Zhang; Hai Ren; Qinglin Wang (Journal of Fish Biology, 2026)
A feeding trial was carried out to investigate the effects of dietary serine on feeding, growth, biochemistry composition, hepatosomatic histological structure and metabolism of taurine synthesis in turbot ( Scophthalmus maximus L.) (2.0 ± 0.01 g) fed plant protein‐based diets. A fishmeal‐based control diet (DietFM) and another two isonitrogenous and isolipidic plant‐based diets containing 0.0% (DietPP) and 3.0% (DietS‐3%) serine were formulated and fed twice daily (06:30 and 18:30) to fish in triplicate groups for 9 weeks. Feed intake in fish fed DietS‐3% was notably higher than that in fish fed DietPP ( p p > 0.05). No significant difference ( p > 0.05) was found with the increase of dietary serine in final body weight, specific growth rate, weight gain rate, feed efficiency ratio, protein efficiency ratio and survival rate when a significant increase ( p p p > 0.05). A significant increase ( p p > 0.05) in fish fed DietS‐3% showed no obvious difference with those of fish fed DietPP ( p > 0.05). The cellular morphology and cell stripes in liver of fish fed diets with 3% serine inclusion were closer to that of fish fed DietFM. Considering the results, 3% serine supplementation in a high plant protein diet significantly increased feeding, mineral accumulation, body taurine content of turbot and obviously improved hepatosomatic histological structure. It is inferred that serine in a taurine‐deficient diet can probably convert to taurine to some degree in juvenile turbot, and the transformation differs with tissue distinction.

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Prediction and analysis of polyvinylidene fluoride membrane pyrolysis reaction based on machine learning framework - Hong Su; Yadong Ge; Xiaohua Wang; Lan Mu; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Post-synthetic acid treatment of aqueous synthesized bimetallic Ce/Zr MOF-801 enables efficient oxidative desulfurization of model fuels - Liang Chu; Zhaokun Wang; Zhaohui Liu; Teng Zhao; Liyan Wang; Mu Yang; Ge Wang (Fuel, 2025)

Hydrogel-engineered platforms for efficient solar interfacial evaporation: Current status and future directions - Junnan Jiang; Heyu Jin; Yao Lu; Xiaohua Liu; Hongyu Ge; Lin Mu (Journal of Water Process Engineering, 2025)

Global changes in potential evapotranspiration (1992–2020) and associated drivers: Shuttleworth-Wallace model-based analysis - Zaoying Bi; Shanlei Sun; Yi Liu; Ge Sun; Mengyuan Mu; Xiaoyuan Li; Jinjian Li; Yibo Liu; Yang Zhou; Botao Zhou; Haishan Chen (Journal of Hydrology, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Multi-constraint analysis reveals distinct aerosol effects on high cloud properties at SACOL and SGP sites - Yang Xia; Jinming Ge; Qingyu Mu; Yue Hu; Nan Peng; Ziyang Qin; Xiang Li; Chi Zhang; Bochun Liu (Atmospheric Research, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

From error ellipse to Bayesian estimation: Strategies for optimizing T-W diagrams in UPb dating - Yao Mu; Can Ge; Fangyue Wang; Xiuyu Li; He Sun; Haiou Gu; Feng Yuan (Geochemistry, 2025)

Defective hierarchical porous Ce-UiO-66 excites phosphotungstic acid for superior low-temperature oxidative desulfurization - Liang Chu; Zhaokun Wang; Teng Zhao; Mu Yang; Ge Wang (Journal of Hazardous Materials, 2025)

SLC39A10 is a key zinc transporter in T cells and its loss mitigates autoimmune disease - Yichang Shao; Qingdian Mu; Rong Wang; Hongbin Luo; Zijun Song; Pengfei Wang; Jingshu Song; Chaodong Ge; Jiyan Zhang; Junxia Min; Fudi Wang (Science China Life Sciences, 2025)

Marine redox evolution and organic matter accumulation in the end Guadalupian in NE Sichuan, South China - Xiaotong Ge; Baojian Shen; Daizhao Chen; Yali Liu; Ziwen Jiang; Mu Liu; Xun Ge (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Dynamic responses and adsorption mechanisms of Chlamydomonas reinhardtii extracellular polymeric substances under Cd, Cu, Pb, and Zn exposure - Chonghua Li; Peihuan Li; Hongxuan Fu; Zijian She; Chunhua Zhang; Yichun Li; Mu Zhang; Ying Ge (Environmental Pollution, 2025)

Hyperspectral image classification based on faster residual multi-branch spiking neural network - Yahui Li; Yang Liu; Rui Li; Liming Zhou; Lanxue Dang; Huiyu Mu; Qiang Ge (Computers & Geosciences, 2025)

Ultralow nano-hierarchical filler loadings enhance the energy storage performance of PEI-based nanocomposites - Zijun Mu; Jin Qian; Guanglong Ge; Simin Wang; Hairui Bai; Guohui Li; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Occurrence and ecological risks of organophosphate esters in the sediments of Hangzhou Bay and the East China Sea - Peng Zhang; Yaqing Cui; Ren Shi; Jing Wang; Linke Ge; Qinglin Mu (Marine Pollution Bulletin, 2025)

Selective removal of ligand in bi-linker MIL-125 by pyrolysis method to improve the oxidative desulfurization - Zhi Huang; Junzhen Guo; Liang Chu; Haibin Yang; Liyan Wang; Zhaokun Wang; Zhaohui Liu; Mu Yang; Ge Wang (Fuel, 2025)

An isolate of human blood-associated partitivirus naturally infects the phytopathogenic fungus Bipolaris maydis - Kun Zhang; Ge Mu; Weilan Wu; Peng Wang; Jun Shang; Changquan Li; Qingchao Deng; Shouguo Fang; Haoran Wang; Songbai Zhang (Archives of Virology, 2025)

Endoplasmic reticulum stress and Ca2+ dysregulation in response to ammonia nitrogen exposure could be alleviated by dietary fermented mulberry leaf meal in Megalobrama amblycephala - Wenqiang Jiang; Linjie Qian; Qiaoqiao Mu; Yan Lin; Siyue Lu; Zhengyan Gu; Huaishun Shen; Xianping Ge; Linghong Miao (Aquaculture, 2024)

Association of ambient ozone exposure with early cardiovascular damage among general urban adults: A repeated-measures cohort study in China - Qiyou Tan; Min Zhou; Xiaojie You; Jixuan Ma; Zi Ye; Wendi Shi; Xiuqing Cui; Ge Mu; Linling Yu; Weihong Chen (Science of The Total Environment, 2024)

Longitudinal joint effects of polycyclic aromatic hydrocarbons exposure and genetic susceptibility on fasting plasma glucose: A prospective cohort study of general Chinese urban adults - Xiuquan Nie; Mengyi Wang; Shijie Yang; Ge Mu; Zi Ye; Min Zhou; Weihong Chen (Environmental Pollution, 2024)

Evaluating and enhancing the applicability of thermal comfort indices in diverse outdoor environments using Bayesian and random forest regression - Wenqiang Jing; Jiayan Liu; Zeming Qin; Teng Mu; Zhemin Ge; Yuting Dong (Energy and Buildings, 2024)

NHX5/NHX6/SPY22 complex regulates BRI1 and brassinosteroid signaling in Arabidopsis - Jun Shang; Guoxiu Mu; Yuting Qi; Xiao Zhang; Wei Shen; Yujie Xie; Mingrui Ge; Yu He; Feng Qiao; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

A new type of dolomicrite envelope formed in Oligocene lacustrine sediments and its significance for preserving porosity, Bohai Bay Basin, North China - Caineng Mu; Xiaobo Huang; Liya Da; Anqing Chen; James G. Ogg; Huan Lu; Yuzhu Ge; Jian Luo; Siyu Xiong; Haiyang Cao; Mingcai Hou (Sedimentary Geology, 2024)

Enhancing energy yield and reducing environmental impact through co-hydrothermal carbonization of undehydrated sewage sludge and fungus bran - Shuai Guo; Jiyou Mu; Long Gao; Liya Ge; Grzegorz Lisak (Journal of Environmental Chemical Engineering, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Microalgae-derived hydrogels/membranes for phosphorus removal and recovery from aquaculture tailwater: Waste utilization and phosphorus recycling - Aihua Zhang; Shihao Fang; Mengni Ge; Jianfeng Zhang; Huan Xi; Yidan Xu; Zhuofan Gao; Zhuo Huang; Mu Liu (Bioresource Technology, 2024)

Effects of straw management and N levels on gross nitrogen transformations in fluvo-aquic soil of the North China Plain - Guocui Ren; Xianfeng Zhang; Jinbo Zhang; Lan Mu; Xiuli Xin; Yiming Yun; Anning Zhu; Shuchun Ge (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Akkermansia muciniphila Protects Against Antibiotic-Associated Diarrhea in Mice - Shenyin Liu; Suying Zhao; Zhiwei Cheng; Yilin Ren; Xinyi Shi; Jing Mu; Xiangyang Ge; Yuan Dai; Lei Li; Zhan Zhang (Probiotics and Antimicrobial Proteins, 2024)

The superiority of hydrophilic polyurethane in comammox-dominant ammonia oxidation during low-strength wastewater treatment - Yunlong Li; Zimin Chai; Chao Song; Jin Chen; Ailu Gu; Guangli Mu; Ruxin Ge; Maosheng Zheng (Science of The Total Environment, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Modulator-assisted solvent-free synthesis of amorphous zirconium terephthalate catalyst for efficient oxidative desulfurization - Liang Chu; Junzhen Guo; Zhaokun Wang; Haibin Yang; Zhaohui Liu; Zhi Huang; Liyan Wang; Mu Yang; Ge Wang (Journal of Hazardous Materials, 2024)

Upcycling crab shell waste into biochar for treatment of palm oil mill effluent via microwave pyrolysis and activation - Yan Yang; Shin Ying Foong; Yifeng He; Rock Keey Liew; Nyuk Ling Ma; Peter Nai Yuh Yek; Shengbo Ge; Mu. Naushad; Su Shiung Lam (Environmental Research, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Contrasting characteristics of continental and oceanic deep convective systems at different life stages from CloudSat observations - Jinming Ge; Xiaoyu Hu; Qingyu Mu; Bochun Liu; Zeen Zhu; Jiajing Du; Jing Su; Qinghao Li; Chi Zhang (Atmospheric Research, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Application of carboxymethyl cellulose sodium (CMCNa) in maize–wheat cropping system (MWCS) in coastal saline-alkali soil - Ge Li; Yuyang Shan; Weibo Nie; Yan Sun; Lijun Su; Weiyi Mu; Zhi Qu; Ting Yang; Quanjiu Wang (Science of The Total Environment, 2024)

Revealing the release and migration mechanism of heavy metals in typical carbonate tailings, East China - Rong Zhao; Xiong Wu; Ge Zhu; Xiao Zhang; Fei Liu; Wenping Mu (Journal of Hazardous Materials, 2024)

Longitudinal association of polycyclic aromatic hydrocarbons and genetic risk with lung function - Min Zhou; Shijie Yang; Limin Cao; Wencan Dai; Xiuquan Nie; Ge Mu; Xiaokang Zhang; Bin Wang; Jixuan Ma; Dongming Wang; Tingming Shi; Chaolong Wang; et al. (Environmental Pollution, 2024)

A comprehensive observation on the pollution characteristics of peroxyacetyl nitrate (PAN) in Beijing, China - Hailiang Zhang; Shengrui Tong; Wenqian Zhang; Yanyong Xu; Mingzhu Zhai; Yucong Guo; Xin Li; Lili Wang; Guiqian Tang; Zirui Liu; Bo Hu; Chengtang Liu; et al. (Science of The Total Environment, 2023)

Nano-biochar uptake and translocation by plants: Assessing environmental fate and food chain risk - Yuliang Li; Chenghao Ge; Cheng Cheng; Xiaolei Wang; Dunfeng Si; Chunyi Mu; Min Wang; Hongbo Li; Dongmei Zhou (Science of The Total Environment, 2023)

A sustainable strategy to transform cotton waste into renewable cellulose fiber self-reinforcing composite paper - Chan Wang; Jinhui Su; Taoyuan Liu; Shengbo Ge; Rock Keey Liew; Hui Zhang; Mu Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Wei Fan (Journal of Cleaner Production, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Self-assembly of Fe-MOF on vermiculite nanosheets with enhanced catalytic activity - Haibin Yang; Junzhen Guo; Liang Chu; Zhi Huang; Zhaohui Liu; Liyan Wang; Zhaokun Wang; Mu Yang; Ge Wang (Applied Clay Science, 2023)

Foliar application of selenium nanoparticles alleviates cadmium toxicity in maize (Zea mays L.) seedlings: Evidence on antioxidant, gene expression, and metabolomics analysis - Min Wang; Chunyi Mu; Yuliang Li; Yixuan Wang; Wenyan Ma; Chenghao Ge; Cheng Cheng; Gaoling Shi; Hongbo Li; Dongmei Zhou (Science of The Total Environment, 2023)

Nitrification-denitrification co-metabolism in an algal-bacterial aggregates system for simultaneous pyridine and nitrogen removal - Xiaoyu Zhang; Dan Chen; Xinying Hou; Na Jiang; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

Degradation of levofloxacin from antibiotic wastewater by pulse electrochemical oxidation with BDD electrode - Tao Xu; Xiting Tang; Meiting Qiu; Xiaoliu Lv; Yang Shi; Yihui Zhou; Yanfei Xie; Mu. Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Shengbo Ge (Journal of Environmental Management, 2023)

Preparation of porous hollow spherical MoOX/C catalyst for efficient extraction and oxidative desulfurization - Junzhen Guo; Baozhen Li; Danfeng Zhao; Liang Chu; Haibin Yang; Zhi Huang; Zhaohui Liu; Mu Yang; Ge Wang (Chemical Engineering Journal, 2023)

Unraveling the intracellular and extracellular self-defense of Chlorella sorokiniana toward highly toxic pyridine stress - Xinying Hou; Yan Li; Xiaoyu Zhang; Shijian Ge; Yang Mu; Jinyou Shen (Bioresource Technology, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Rotifer distribution patterns in relation to dissolved organic matter in the middle reaches of Huai River Basin during the dry season - Leilei Luan; Liangmin Gao; Xudong Chen; Juan Ge; Ming Mu; Xiaoqing Chen; Xinglan Zhao; Zhen Zhang; Haiqiang Zhang (Environmental Science and Pollution Research, 2023)

Aspirin alleviates cisplatin-induced acute kidney injury through the AMPK-PGC-1α signaling pathway - Danning Tong; Enshuang Xu; Ruidong Ge; Mengxin Hu; Shengzi Jin; Jing Mu; Yun Liu (Chemico-Biological Interactions, 2023)

The dynamic amplification effect of a site with earth fissures: a case study in the Taiyuan Basin, China - Jiang Chang; Yahong Deng; Ge Cao; You Xuan; Nainan He; Xunchang Zhao; Huandong Mu (Journal of Seismology, 2023)

Cross-sectional and longitudinal relationships between ozone exposure and glucose homeostasis: Exploring the role of systemic inflammation and oxidative stress in a general Chinese urban population - Qiyou Tan; Bin Wang; Zi Ye; Ge Mu; Wei Liu; Xiuquan Nie; Linling Yu; Min Zhou; Weihong Chen (Environmental Pollution, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

Microtremor-based analysis of the dynamic response characteristics of a site containing grouped earth fissures - Yahong Deng; You Xuan; Huandong Mu; Jiang Chang; Ge Cao; Nainan He; Xunchang Zhao; Longfei Sun (Earthquake Engineering and Engineering Vibration, 2023)

Nicotine exposure exacerbates silica-induced pulmonary fibrosis via STAT3-BDNF-TrkB-mediated epithelial-mesenchymal transition in alveolar type II cells - Haoming Chen; Xinrong Tao; Hangbing Cao; Bing Li; Qixian Sun; Wenyang Wang; Yuanjie Zou; Min Mu; Huihui Tao; Yehong Zhao; Deyong Ge (Food and Chemical Toxicology, 2023)

Associations of selenium exposure with blood lipids: Exploring mediating DNA methylation sites in general Chinese urban non-smokers - Xiuquan Nie; Ge Mu; Yanjun Guo; Shijie Yang; Xing Wang; Zi Ye; Qiyou Tan; Mengyi Wang; Min Zhou; Jixuan Ma; Weihong Chen (Science of The Total Environment, 2023)

Short-term impacts of air pollution on the platelet-lymphocyte ratio and neutrophil-lymphocyte ratio among urban adults in China - Weihong Qiu; Heng He; Bin Wang; Dongming Wang; Ge Mu; Tao Xu; Min Zhou; Zi Ye; Jixuan Ma; Weihong Chen (Journal of Environmental Sciences, 2023)

Modification of anaerobic digestion model No.1 with Machine learning models towards applicable and accurate simulation of biomass anaerobic digestion - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Hong Su; Beibei Yan; Guanyi Chen (Chemical Engineering Journal, 2023)

Simulation of integrated anaerobic digestion-gasification systems using machine learning models - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Rui Liang; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Beibei Yan; Guanyi Chen (Bioresource Technology, 2023)

External-loop split-type dynamic membrane photobioreactor for the treatment of high-strength pyridine wastewater: Improved photosynthetic oxygenation and mitigated membrane fouling - Xiaoyu Zhang; Na Jiang; Xinying Hou; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

Excellent catalytic performance over acid-treated MOF-808(Ce) for oxidative desulfurization of dibenzothiophene - Liang Chu; Junzhen Guo; Zhi Huang; Haibin Yang; Mu Yang; Ge Wang (Fuel, 2023)

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

Amphiphilic halloysite nanotube enclosing molybdenum oxide as nanoreactor for efficient desulfurization of model fuels - Junzhen Guo; Liang Chu; Haibin Yang; Zhi Huang; Mu Yang; Ge Wang (Chemical Engineering Journal, 2023)

Comparisons of cirrus clouds and their linkages to meteorology at the SACOL and the SGP sites - Zixiang Dong; Jinming Ge; Ang Gao; Zeen Zhu; Jialin Yan; Qingyu Mu; Jing Su; Xuan Yang; Xiaoyu Hu (Atmospheric Research, 2023)

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

Dynamic characteristics of fault-controlled earth fissure sites in Jingyang County, Weihe Basin, China - You Xuan; Yahong Deng; Jiang Chang; Huandong Mu; Ge Cao (Acta Geophysica, 2022)

Molecular cloning, characterization and expression analysis of P53 from high latitude fish Phoxinus lagowskii and its response to hypoxia - Jing Wang; Xi Chen; Xinrui Ge; Zhen Wang; Weijie Mu (Fish Physiology and Biochemistry, 2022)

Short-term effects of real-time individual fine particulate matter exposure on lung function: a panel study in Zhuhai, China - Zi Ye; Bin Wang; Ge Mu; Yun Zhou; Weihong Qiu; Shijie Yang; Xing Wang; Zhuang Zhang; Weihong Chen (Environmental Science and Pollution Research, 2021)

Sources of 24-h personal exposure to PM2.5-bound metals: results from a panel study in Wuhan, China - Xing Wang; Bin Wang; Lili Xiao; Xiuqing Cui; Xingzu Cen; Shijie Yang; Ge Mu; Tao Xu; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

Temperature variations evidenced by records on the latest spring snowing dates in Hangzhou of eastern China during 1131-1270AD - Haolong Liu; Junhu Dai; Junhui Yan; Fanneng He; Quansheng Ge; Chongxing Mu (Journal of Geographical Sciences, 2020)

Exposure to Prorocentrum minimum Induces Oxidative Stress and Apoptosis in the Ridgetail White Prawn, Exopalaemon carinicauda - Cuimin Mu; Qianqian Ge; Jian Li (Journal of Ocean University of China, 2019)

Astaxanthin enhances hematology, antioxidant and immunological parameters, immune-related gene expression, and disease resistance against in Channa argus - Mu-Yang Li; Xin-Yu Liu; Chang-Ge Xia; Gui-Qin Wang; Dong-Ming Zhang (Aquaculture International, 2019)

Remote sensing monitoring of the suspended particle size in Hongze Lake based on GF-1 data - Shaohua Lei; Di Wu; Yunmei Li; Qiao Wang; Changchun Huang; Ge Liu; Zhubin Zheng; Chenggong Du; Meng Mu; Jie Xu; Heng Lv (International Journal of Remote Sensing, 2019)

Long-term observation of cyanobacteria blooms using multi-source satellite images: a case study on a cloudy and rainy lake - Meng Mu; Chuanqing Wu; Yunmei Li; Heng Lyu; Shengzhong Fang; Xiang Yan; Ge Liu; Zhubin Zheng; Chenggong Du; Shun Bi (Environmental Science and Pollution Research, 2019)

Tempo-spatial dynamics of water quality and its response to river flow in estuary of Taihu Lake based on GOCI imagery - Chenggong Du; Yunmei Li; Qiao Wang; Ge Liu; Zhubin Zheng; Meng Mu; Yuan Li (Environmental Science and Pollution Research, 2017)

Antioxidant response of ridgetail white prawn Exopalaemon carinicauda to harmful dinoflagellate Prorocentrum minimum exposure and its histological change - Cuimin Mu; Xianyun Ren; Qianqian Ge; Jiajia Wang; Jian Li (Journal of Ocean University of China, 2017)

Genome-wide analysis of shoot growth-associated alternative splicing in moso bamboo - Long Li; Tao Hu; Xueping Li; Shaohua Mu; Zhanchao Cheng; Wei Ge; Jian Gao (Molecular Genetics and Genomics, 2016)

IL-1α-induced microvascular endothelial cells promote neutrophil killing by increasing MMP-9 concentration and lysozyme activity - Xiaoye Liu; Hong Dong; Mingming Wang; Ying Gao; Tao Zhang; Ge Hu; Huiqing Duan; Xiang Mu (Immunologic Research, 2016)

Spectrum analysis of wind profiling radar measurements - Zheng Ruan; Ruiqi Mu; Ming Wei; Runsheng Ge (Journal of Meteorological Research, 2014)

Clinical and laboratory characteristics of patients having amyloidogenic transthyretin deposition in osteoarthritic knee joints - Ya-Jun Gu; Peng Ge; Yun Mu; Jin-Hai Lu; Fang Zheng; Xu-Guo Sun (Journal of Zhejiang University-SCIENCE B, 2014)

New cycloartane triterpene glycosides from Beesia calthaefolia - Hong-Jie Li; Li-Hua Mu; Xian-Zhe Dong; Xiao-Yue Ge; Ping Liu (Natural Product Research, 2013)

The effective expression of xylanase gene in Candida utilis by 18S rDNA targeted homologous recombination in pGLR9K - Wang Wei; Yang Hong-Lan; Bao HuiFang; Zhang Daoyuan; Shan Qi-mu-ge; Andrew J. Wood (Molecular Biology Reports, 2010)